(untitled) (IAHS Medical Journal, 2022)
Background: Biliary ascariasis is common, not only in under developed countries, but also in other parts of the world and should be considered as a differential diagnosis in patients with biliary pain or acute cholangitis, even at centers where biliary ascariasis is not endemic. This study aimed to assess the clinical and ultrasonic features and management of such patients admitted in a tertiary hospital of Bangladesh. Materials and methods: Fifty cases of biliary ascariasis admitted in the Medicine Ward of Chittagong Medical College Hospital from January to June 2017 were included in the study. Patients were initially treated conservatively with Tab albendazole (400mg) twelve hourly for 3 days. Serial ultrasonography was done to see the position of worm in the biliary tree. Results: Majority (68%) of the respondents was in 18 to 35 years age group and 78% were female. Abdominal pain and vomiting were the common presenting features present respectively in 100%, and 78% of the cases. Pain was relieved in 92% of the cases and worm was present in biliary tree only in 4% cases in follow-up sonography. Forty two (84%) of the patients were cured with conservative treatment and the rest 16% needed endoscopic or surgical treatment. Conclusion: It is concluded that conservative treatment with albendazole is very effective and safe in patients with biliary ascariasis. IAHS Medical Journal Vol 4(2), December 2021; 8-11